ARTISTIC AND AESTHETIC ANALYSIS OF ABDULKHAMID CHOULPON’S NOVEL NIGHT AND DAY - Jumanova Shohista Rofiyevna (Western European Studies, 2025)
Abdulhamid Choulpon’s unfinished novel Night and Day is widely recognized as the first socio-psychological work in Uzbek prose. This paper analyzes the novel’s artistic, ideological, and symbolic dimensions, focusing on how Choulpon critiques patriarchal norms, colonial oppression, and religious hypocrisy through a psychologically rich narrative. Using a close reading method, the study examines key characters, especially, Zebi—as representations of Uzbek women’s inner lives, societal constraints, and spiritual resilience. The central metaphor of “night” and “day” reflects the broader national struggle between ignorance and awakening. Through natural imagery, contextual antonymy, and culturally embedded dialogue, Choulpon crafts a realistic portrayal of early 20th-century Uzbek society. The novel’s lyrical style, combined with its ideological critique, positions Night and Day as a significant work of literary resistance and cultural introspection, reflecting the psychological and social awakening of a nation in transition
Keywords: Uzbek literature; socio-psychological novel; symbolism; patriarchal critique